Fibra em detergente neutro em dietas com palma forrageira para cabras leiteiras - Sousa, Niraldo Muniz de (2014)
The objective of this study was to evaluate the effect of the addition of neutral detergent fiber arising forage (NDF) in diets with forage cactus (Opuntia ficus indica mill) for dairy goats. 15 goats were distributed in a Latin square design 5 × 5, using five levels of NDF (D1: 11.98%; D2: 18.31%; D3: 23.68%; D4: 28.76% and D5 : 32.12% NDF arising from Tifton hay) as an independent variable. The dry matter (DM), crude protein (CP), ether extract (EE), neutral detergent fiber (NDF), non-fiber carbohydrates (NFC), total digestible nutrients (TDN) linearly decreased with increasing levels of NDF. Changes in diets fiber concentrations improved in a way with the increase of NDF levels of digestibility of DM, CP, NDF, EE and NFC. The variation in the levels of NDF, influence the consumption of supplied water. There was a linear increase in the consumption of water supplied in relation to increased dietary NDF level ranging 1.87 kg / day. Water consumption in the diet even with negative linear effect on average daily nutrient intake there was no linear effect in relation to NDF levels. The yield was not influenced by addition of fiber. However, feed conversion improved with increased NDF in the diet. The concentrations of milk components (fat, protein, lactose, total dry layer and ash) did not change with the fiber levels of diets. The pH and acidity in Dornic degrees, remained within the requirement by Instruction. For frequency of physiological parameters was observed that there was no difference (P> 0.05). In the conditions were conducted the experiment, the values of consumption and digestibility of nutrients promote linearly with the increase of NDF content, not observed, therefore, minimum and maximum capacity fiber intake. Fiber content used in this work does not cause effect on milk yield and composition, and studies should be conducted with greater variations of NDF.